An Introduction to the Foreign Trade of Mesopotamia In the Light of Cuneiform Documentation of the Third and Second Millennium BC. - A. Al-Mutawalli, Nawala (Al-Adab Journal, 2018)
Ancient Iraq is very well known as an agricultural economic country, especially, the middle and the southern parts of Mesopotamia, which was called “the Land of Sumer and Akkad “, it’s a very rich agricultural country. Sumer’s economy was based on agriculture, fishing, and cattle and sheep breeding. Lived on the products of the fertile, irrigated soil, and this situation was clearly reflected in the cuneiform texts unearthed from many sites from the third and second millennium BC. And due to the young geological composition of Mesopotamia, the alluvial plain of ancient Sumer lacked so much important raw materials, these of materials were needed by the craftsmen of Sumer and Akkad for the industry, works of art and daily life. These raw material were, deferent kinds of stone, timber, and metal, therefore, the need for these materials led to exchange what the people had from the agricultural production and industrial goods and material produced by the workshops of temple or palace, such as: animal hides, leather manufactures, wool, oil, cereals, dates, textile, wild and domesticated animals,…etc., also what not existing in the country ([i]) Leemans, W.F., "The Importance of Trade", Iraq-39, (1977), p. 4. Al-Hashimi, Rihdah Jawad, "Obsidian Stone and the Origin of Trade" Sumer-28, (1972), p. 203ff.